The unconsoled eaudiobook - Ishiguro, Kazuo (Tantor Media, 2017)
From the winner of the Nobel Prize in Literature and author of the Booker Prize–winning novel The Remains of the Day , here is a novel that is at once a gripping psychological mystery, a wicked satire of the cult of art, and a poignant character study of a man whose public life has accelerated beyond his control. The setting is a nameless Central European city where Ryder, a renowned pianist, has come to give the most important performance of his life. Instead, he finds himself diverted on a series of cryptic and infuriating errands that nevertheless provide him with vital clues to his own past. In The Unconsoled Ishiguro creates a work that is itself a virtuoso performance, strange, haunting, and resonant with humanity and wit.